2004
DOI: 10.1001/archpsyc.61.6.597
|View full text |Cite
|
Sign up to set email alerts
|

Association of Specific Haplotypes of D2 Dopamine ReceptorGene With Vulnerability to Heroin Dependence in 2 Distinct Populations

Abstract: These results strongly support a role of DRD2 as a susceptibility gene with heroin dependence in Chinese patients and was associated with low risk of heroin dependence in Germans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
64
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(73 citation statements)
references
References 34 publications
7
64
0
Order By: Relevance
“…Of interest is the fact that Neville et al [2004] have localized the TaqI A polymorphism to a region approximately 9.5 kb upstream from the DRD2 gene in the Ankyrin (ANKK1) gene. Two studies found evidence for linkage disequilibrium between the TaqI A and the C957T polymorphisms [Duan et al, 2003;Xu et al, 2004] as was found in the present study. This suggests those previously reported positive associations between various addictions (e.g., alcohol dependence and nicotine dependence) and the TaqI A polymorphism may have been the result of variations in the C957T polymorphism which is known to have functional effects on dopaminergic availability.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Of interest is the fact that Neville et al [2004] have localized the TaqI A polymorphism to a region approximately 9.5 kb upstream from the DRD2 gene in the Ankyrin (ANKK1) gene. Two studies found evidence for linkage disequilibrium between the TaqI A and the C957T polymorphisms [Duan et al, 2003;Xu et al, 2004] as was found in the present study. This suggests those previously reported positive associations between various addictions (e.g., alcohol dependence and nicotine dependence) and the TaqI A polymorphism may have been the result of variations in the C957T polymorphism which is known to have functional effects on dopaminergic availability.…”
Section: Discussionsupporting
confidence: 88%
“…Also, Lerman et al [2006] found that nicotine dependent individuals homozygous for the -141C Ins/Del showed an improved treatment response to buproprion. A significant case/control association between heroin dependence and allelic variation in both -141C Ins/Del and A-241G has been reported in a Chinese sample [Xu et al, 2004] though the results were not seen in a German sample studied by this group of investigators.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…They were recruited from a study on genetic influences on vulnerability to heroin dependence (Xu et al, 2004). In conjunction with a five-year follow up, only subjects who were abstinent for at least one year were considered for the present study (mean abstinence duration (SD)=18.93 (±20.45) months).…”
Section: Participantsmentioning
confidence: 99%
“…[5][6][7][8][9] These include variants in genes coding for two receptors of the opioid system, the m 10-12 and k opioid receptors. 13 Other variants that have been found to be associated with opiate addiction are located in and around the dopamine D2 [14][15][16] and D4 receptors, [17][18][19][20] the serotonin transporter, 21,22 the serotonin 1B receptor 23 and genes for the enzyme catechol-O-methyltransferase. 24,25 Studies have provided evidence that several chromosomal regions are linked to the vulnerability to develop heroin, alcohol, nicotine or other drug abuse or addiction.…”
Section: Introductionmentioning
confidence: 99%